الجريمة الجمركية بين القواعد العامة والتوجهات الحديثة في السياسة الجنائية - زيان محمد أمين (My University, 2019)
ملخص الأطروحة باللغة العربية المرتكز دراسة البحث الموسوم بـ " الجريحة الجمركية بين القواعد العامة والتوجهات الحديثة في السياسة الجنائية " على مناقلة وتحليل ما قريع المشرع الجزائري من أحكام قانونية وتنظيمية، في إطار تعديل قانون الجمارك الجزاري بموجب القانون 17-04 ، والقانون المتعلق بمكافحة التهريب المجدل بمرين الأمر 10-01 - وما حديث به القواعد العامة نفسها من تعديلات، مست الدستور الجزائري سنة 2016 موجب تعديلة بالقانون رقم 16 - 01، وقانون العقوبات بموجب القانون 16 12 وقانون الإجراءات الجزائية بموجب القانون 18 00 ويكشف هذا البحث، أن المشرع الجزائري في معالونه للجريمة الجمركية ، اعتمد مزيجا بين القواعد العامة وخصوصيات الفنون الجمركي " التقنيات والفنون الجمركية ، يشكل بيران أن المشرع الجزائري يأخذ القاعدة من المبادئ العامة في أغلب الأحوال ، لكن مع تطويرة بما يقدم الأهداف الحديثة للسياسة الجنائية المتبعة في إطار مكافحة هذا النوع من الإجرام، حتى ولو كان ذلك على حساب قاعدة الموازنة بين مقتديات السلطة العامة التي تستلزم مكافحة الدولة للجريمة بكل ما أوتيت من قوة، ومقتنيات حماية الحقوق والحريات العربية المحمية بأقوى نص في الهرم القانوني للدولة، وهو النص الدستوري الكرايب يقع على خالقها ، على اختبار أنه لا يمكن لأحد اليوم الإتكار أن يعال القوانين الجمركية الحديثة، أصبح محلا بقدرتها على مجاراة التطورات الحاصلة في ارتكاب هذا النوع من الإجراء، ومن هذا المنطلق تظهر الخصوصية Customs Crime Between general Rules and modern trends in criminal policy. Abstract of the thesis in English The research study, entitled "The costones crime hetween the general rules and the moder tremdh in criminal policy", is based on the discussion and analysis of the legal and regulatory previsions of the Algerian legislator, under the amendment of the Algerian Customs Code within the law 17-04, And ander the Order 10-21, and even with the same general rades which were amended, namely the amended Algerian constitution of 2016 by as amendment Ne 16-01, and the Penal Code ander Law 16-82, and the Code of Criminal Procedures under Low 18-06. Thời xhady, infact, reveals that the Algerian legislator, in treating the customs crime, adopted a combination of general rules and the customs low, "customs and artistic techniques", to prove that the Algerian legislator takes the rule from general principles in most cases, but with a kind of development to serve the modern objectives of criminal policy in the fight against this type of crime, Even if this is af the expense of the balance between the requirements of the public authority, which requires the state to combat the crime with all its might, and the requirement for the protection of individual rights and freedoms protected by the strongest text in the legat hierarchy of the Stute, the constinational text, as a duty; no one can deny today that the competition of modern customs laws has been suspended by in ability to keep updated with the developments in the commission of sach criminality, and from this particular point of view, the privacy of customs crime emerges Ottoms Crime-Ceston Swaggling-Gamerul Rules-Criminal Policy-Castити Інгресtiоn Presumption of innocence-Tax Lawsail-General Research-Castans Tax
Keywords: الجريمة الجمركية - التهريب الجمركي - القواعد العامة - السياسة الجنائية - التفتيش الجمركي - قرينة البراءة - الدعوى الجبائية - الأبحاث العامة - الغرامة الجمركية